Global, regional, and national burden and trends of intracerebral hemorrhage among adolescents and young adults aged 15–39 years from 1990 to 2021: a comprehensive trend analysis based on the global burden of disease study 2021 - Liu, Xuanchen; Yang, Xiaoxiong; Meng, Yaoju; Wen, Boyang; Yan, Kun; Zhang, Qiyi; Wang, Junhao; Su, Yifei; Niu, Xiaochen; Song, Yingda; Cheng, Rui; Ji, Hongming; et al. (Frontiers in Neurology, 2025)
BackgroundIntracerebral hemorrhage (ICH) poses a significant health challenge, notably affecting adolescents and young adults (AYAs) aged 15–39 years. Despite advancements in medical technology, the global burden of ICH remains substantial, influenced by lifestyle factors, socioeconomic conditions, and disparities in healthcare access. This study leverages data from the 2021 Global Burden of Disease (GBD) to conduct a comprehensive analysis of ICH trends and burdens at global, regional, and national levels, emphasizing the role of the Social Development Index (SDI).MethodsWe utilized data from the GBD 2021 to assess the incidence, prevalence, mortality, and disability-adjusted life years (DALYs) associated with ICH from 1990 to 2021, covering 204 countries and regions. Age-standardized rates were calculated to ensure comparability. Temporal trends were evaluated using Joinpoint regression analysis, and future projections were made using a Bayesian Age-Period-Cohort model.ResultsIn 2021, 246,938 new cases of ICH were reported among the global AYAs population, reflecting a decline in age-standardized incidence rates from 11.85 per 100,000 in 1990 to 8.14 in 2021. Prevalence rates also decreased from 124.44 to 94.58 per 100,000. Mortality rates and DALYs exhibited similar downward trends. Significant regional disparities were observed, with high SDI regions experiencing lower ICH burdens than low SDI regions, highlighting the influence of socioeconomic factors and healthcare access.ConclusionWhile the global burden of ICH among AYAs has declined, significant disparities persist, particularly in regions with lower SDI. To further mitigate the impact of ICH, public health initiatives should focus on enhancing healthcare infrastructure, promoting health education, and addressing socioeconomic inequalities.